ANALYZING THE CONCEPT OF SELF-ACTUALITATION IN FREEDOM WRITERS MOVIE - Anisha Bunga Armethia Fitriane; Abdilah Nugroho (Jurusan Sastra Indonesia, 2022)
This research analyze the concept of self-actualitation in “The Freedom Writers” movie based on the humanistic approach perceived by Carl Rogers. This study aims to determine the process of developing the self-actualization of one characters in the film “The Freedom Writers” named Eva and how it impacts her social life as a student. The writer used psychological literature for the approach of research. The data used in this paper is a movie entitled “The Freedom Writers” by Richard LaGravenese. This film is adapted from a novel entitled “The Freedom Writers Diary” by Erin Gruwell which is written based on a true story. The result of this paper is showing the self-actualization from Eva Benitez’s character and its provide from the uneducated girl to became one of the diary writer.